2012
DOI: 10.1148/radiol.11110358
|View full text |Cite
|
Sign up to set email alerts
|

Rachitic Changes, Demineralization, and Fracture Risk in Healthy Infants and Toddlers with Vitamin D Deficiency

Abstract: Purpose:To examine radiographic fi ndings in children with vitamin D defi ciency in comparison with biochemical marker levels and prevalence of fractures. Materials and Methods:The parents or guardians of all participants provided written informed consent at the time of enrollment. The institutional review board approved the protocol, and HIPAA guidelines were followed. From a prospective sample of children seen for routine clinical care, 40 children with vitamin D defi ciency (25-hydroxyvitamin D [25-OHD] lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 48 publications
(48 reference statements)
0
22
0
1
Order By: Relevance
“…71 Despite the high prevalence of vitamin D insufficiency in infants and toddlers, rickets is uncommon. 72 The claim that vitamin D deficiency or insufficiency causes skeletal lesions that lead to the incorrect diagnosis of child abuse in infants is not supported in the literature. A systematic clinical, laboratory, and radiologic assessment should exclude that possibility.…”
Section: Vitamin D Deficiency Ricketsmentioning
confidence: 99%
See 1 more Smart Citation
“…71 Despite the high prevalence of vitamin D insufficiency in infants and toddlers, rickets is uncommon. 72 The claim that vitamin D deficiency or insufficiency causes skeletal lesions that lead to the incorrect diagnosis of child abuse in infants is not supported in the literature. A systematic clinical, laboratory, and radiologic assessment should exclude that possibility.…”
Section: Vitamin D Deficiency Ricketsmentioning
confidence: 99%
“…In this population, the reported fracture prevalence was zero. 72 In a study of 45 young children with radiographic evidence of rickets, investigators found that fractures occurred only in those infants and toddlers who were mobile. 77 Fractures were seen in 17.5% of the children, and these children were 8 to 19 months of age.…”
Section: Vitamin D Deficiency Ricketsmentioning
confidence: 99%
“…Perez-Rossello et al identified 26 children with radiographic and biochemical evidence of rickets. At telephone interview follow-up 2-3 years after diagnosis and treatment, no child had sustained a fracture [53]. However, owing to the small number of children included and lack of a healthy control group, it is difficult to draw any conclusions on fracture risk following resolution of rickets.…”
Section: Fracture In Children With Vitamin D Deficiency Ricketsmentioning
confidence: 99%
“…However, this paper did not address causality between low vitamin D levels, without the presence of radiological findings, and fracture risk. A study from Perez-Rosello et al did show that in children with proven low vitamin D-levels and normal skeletal surveys no increase in fracture incidence was noted [6]. Based on their findings the authors concluded that 'In infants and toddlers with vitamin D deficiency, rachitic changes and definite demineralization are uncommon and fracture risk is low'.…”
Section: Dear Editormentioning
confidence: 97%